Investigation on the static and dynamic behavior of BCC lattice structure with quatrefoil node manufactured using fused deposition modelling additive manufacturing. Issue 1 (April 2020) - Azmi, M S; Ismail, R; Hasan, R
Abstract: This paper presents a vibration characteristics of BCC lattice structure with quatrefoil node which has been made using the fused deposition modelling (FDM) additive manufacturing (AM) technique. By conducting vibration testing, the effect of strut diameter design parameter on the natural frequency values of the BCC lattice structure with quatrefoil node is investigated. The results showed that the natural frequency values of the lattice structure material can be greatly affected by the strut diameter sizes due to increase in stiffness as the strut diameter increases. The mathematical equation is also derived to calculate the total area moments of inertia of the lattice structure model and the validity of this developed model is shown through comparison of the results with experimental work of the three-point bending test which shown similar increase trend. Thus, this study provides information on the influence of strut diameter design parameter on its vibration characteristic.